Developing oral nanovaccines for fish: a modern trend to fight infectious diseases. (4th November 2020) - Angulo, Carlos; Tello‐Olea, Marlene; Reyes‐Becerril, Martha; Monreal‐Escalante, Elizabeth; Hernández‐Adame, Luis; Angulo, Miriam; Mazon‐Suastegui, José M.
Abstract: Nanovaccines constitute an innovative approach in vaccinology, enabled by the nanotechnology advances on the synthesis, functionalization and application of nanoparticles for immunization. Currently, several organic materials such as chitosan, poly(lactic‐co‐glycolic acid), nanopoliplexes and virus‐like particles (VLPs) have been used for nanovaccine development to fight against fish diseases. The oral route is the most practical and economical for fish vaccination; thus, several oral vaccine candidates have been developed by using NPs in which the antigen is encapsulated, surface exposed or recombinantly ensembled (VLPs), leading to promising results in terms of protection capacity against infectious diseases. In this review, the state of the art on oral nanovaccine prototypes developed for use in fish was analysed and discussed. Oral nanovaccines have showed remarkably possibilities for application in fish aquaculture, which surely will be adopted by the industry in the following years.